A sub-30 GHz differential-frequency tripler in 22-nm FDSOI technology for FMCW spectrum. (September 2022) - Kumar, Piyush; Stajic, Dario; Narayanan, Rama; Nevzat Isa, Erkan; Maurer, Linus
Abstract: In this work, a wide-band Frequency-Tripler is designed to cover Frequency-Modulated Continuous Wave radar (FMCW) in 22-nm CMOS-FDSOI Technology. The designed frequency Tripler upconverts sub-30 GHz signal to cover a wide-band FMCW spectrum (72–84 GHz). In this paper, the silicon validated results of a VCO combined with the proposed frequency Tripler are presented. The design architecture, EM simulation results, measurement setup and silicon result of our fabricated die are covered in this paper. The designed circuit consumes 20 mA of current at the supply voltage of 800 mV. The Tripler works in the input frequency range from 24 GHz to 32 GHz, delivering a wide-band frequency output of 72–96 GHz. The differential output of VCO is capacitively coupled with the input of the multiplier.